2013
DOI: 10.1002/bies.201300095
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal gene acquisitions by eukaryotes as drivers of adaptive evolution

Abstract: In contrast to vertical gene transfer from parent to offspring, horizontal (or lateral) gene transfer moves genetic information between different species. Bacteria and archaea often adapt through horizontal gene transfer. Recent analyses indicate that eukaryotic genomes, too, have acquired numerous genes via horizontal transfer from prokaryotes and other lineages. Based on this we raise the hypothesis that horizontally acquired genes may have contributed more to adaptive evolution of eukaryotes than previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
114
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 102 publications
(138 reference statements)
7
114
0
3
Order By: Relevance
“…Although such genes should be excluded from phylogenetic data sets, it can be difficult to recognize hidden paralogs and separate them from real orthologs. The same problem concerns genes subjected to horizontal gene transfer (HGT), which seems to be a common process, not only in prokaryotic organisms, but also eukaryotes including Archaeplastida lineages [106][107][108][109][110][111]. Such genes are most likely also present in many alignments analyzed and could cause artificial clustering.…”
Section: Inconsistency Of Archaeplastida Phylogenies In the Context Omentioning
confidence: 99%
“…Although such genes should be excluded from phylogenetic data sets, it can be difficult to recognize hidden paralogs and separate them from real orthologs. The same problem concerns genes subjected to horizontal gene transfer (HGT), which seems to be a common process, not only in prokaryotic organisms, but also eukaryotes including Archaeplastida lineages [106][107][108][109][110][111]. Such genes are most likely also present in many alignments analyzed and could cause artificial clustering.…”
Section: Inconsistency Of Archaeplastida Phylogenies In the Context Omentioning
confidence: 99%
“…This notion was extended in the biological species concept of Dobzhansky (1935) and Mayr (1942), which states that species are reproductively isolated units, implying that adaptive mutations can spread within a species leaving other coexisting species unaffected. Although recent evidence has shown that reproductive boundaries can be leaky (Danchin and Rosso 2012;Syvanen 2012;Schönknecht et al 2013), species are still regarded as congruent genetic and ecological units for sexual eukaryotes, even if hybrids and intermediate forms are common (Mallet 2008). For bacteria and archaea, however, the situation has been marred by several complicating factors that question whether such units can be defined.…”
mentioning
confidence: 99%
“…For us, identifying cases where transfer has amended or added function in the recipient lineage, however rare, represents one of the most exciting prospects of this field of research. Researchers are therefore correct to look for HGT in organisms that are capable of "extraordinary" biological functions, for example colonizing extreme or variant environments in contrast to related taxa (27). However, caution is needed in these endeavors.…”
mentioning
confidence: 99%